La place des sources documentaires dans l’écriture de l’histoire à l’ère du numérique : le cas de l’Encyclopédie raisonnée des techniques du cinéma - Rémy Besson (Les Cahiers de Framespa)
This paper provides both a feedback on the creation of a digital encyclopedia and an epistemological reflection on the writing of history. The feedback concerns the Encyclopedia of Film Techniques and Technologies (of which the author of these lines is the editorial director) conceived within the research partnership TECHNÈS (2015-2022). This editorial experimentation led to the design of a new mode of publishing online. Such a project required the identification of a certain number of unspoken issues present in the controversies around the writing of history in order to identify the two precise points on which the editorial innovation focuses, namely the display of sources and their integration into the writing of history. This Encyclopedia is conceived as an alternative format that aims to make sources visible in the very writing of history by giving them an argumentative function.